f ( x , y , z ) = 2 x 2 + 2 y 2 − 2 z 2 + x y 7 + z 1
There exists three pairwise distinct numbers a , b and c that satisfies
f ( a , b , c ) = f ( b , c , a ) = f ( c , a , b )
Given that a b c = n m , where m and n are positive coprime integers, find the value of m + n
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Or we can form three new equations from first three equations and them adding them all. That can also generate our result, but for that value of a + b + c should be known. Nice solution (+1) :)
Log in to reply
Well, to know the value of a + b + c , this is the shortest method I can find. But yeah, you can add all 3 equations and get the value. Most likely, you already solved the inspiration question if you did that
Log in to reply
I solved it, but ticked the wrong option by mistake. I solved it the way you did, but here I thought in a different way.
Problem Loading...
Note Loading...
Set Loading...
⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ f ( a , b , c ) = 2 a 2 + 2 b 2 − 2 c 2 + a b 7 + c 1 f ( b , c , a ) = 2 b 2 + 2 c 2 − 2 a 2 + b c 7 + a 1 f ( c , a , b ) = 2 c 2 + 2 a 2 − 2 b 2 + c a 7 + b 1 ⟹ 1 ⟹ 2 ⟹ 3
1 = 2 :
2 a 2 + 2 b 2 + 2 c 2 + a b 7 + c 1 = 2 b 2 + 2 c 2 − 2 a 2 + b c 7 + a 1 4 a 2 − 4 c 2 = b c 7 − a b 7 + a 1 − c 1 4 ( a − c ) ( a + c ) = a b c 7 ( a − c ) − a c a − c
Since we know that a = b = c , we know that a − c = 0
Divide the equation by ( a − c ) :
4 ( a + c ) = a b c 7 − a c 1 4 ( a + c ) = a b c 7 − b 4 a b c ( a + c ) = 7 − b ⟹ 4
Do the same thing for 1 = 3 (Note that b − c = 0 as well):
2 a 2 + 2 b 2 + 2 c 2 + a b 7 + c 1 = 2 c 2 + 2 a 2 − 2 b 2 + a c 7 + b 1 4 b 2 − 4 c 2 = a c 7 − a b 7 + b 1 − c 1 4 ( b − c ) ( b + c ) = a b c 7 ( b − c ) − b c b − c 4 ( b + c ) = a b c 7 − b c 1 4 ( b + c ) = a b c 7 − a 4 a b c ( b + c ) = 7 − a ⟹ 5
4 ÷ 5 :
4 a b c ( b + c ) 4 a b c ( a + c ) = 7 − a 7 − b
Note that for the original expression to be defined, a , b , c = 0 , because a , b and c are in denominators. This implies that a b c = 0 as well, and we can cross off the a b c in the equation:
b + c a + c = 7 − a 7 − b ( 7 − a ) ( a + c ) = ( 7 − b ) ( b + c ) 7 a + 7 c − a 2 − a c = 7 b + 7 c − b 2 − b c 7 a − 7 b = a 2 − b 2 + a c − b c ( a − b ) ( a + b ) + c ( a − b ) = 7 ( a − b )
Remember, a − b = 0 as well, so we divide it out
a + b + c = 7 7 − b = a + c ⟹ 6 7 − a = b + c ⟹ 7
Substitute 6 into 4 and 7 into 5
4 a b c ( 7 − b ) = 7 − b 4 a b c ( 7 − a ) = 7 − a
Now, we know that a = b = c . Therefore, if 7 − b = 0 , 7 − a = 0 . This means we can divide one of them. (Note: In fact, the only ordered triple that satisfies f ( a , b , c ) = f ( b , c , a ) = f ( c , a , b ) AND contains a 7 is ( a , b , c ) = ( 7 , 7 , − 7 ) , which does not satisfy the condition a = b = c . You can try proving it.)
4 a b c = 7 − a 7 − a 4 a b c = 1 a b c = 4 1
m = 1 , n = 4 , m + n = 1 + 4 = 5